"A Perilous Venture for Democracy": Soldiers, Sexual Purity, and American Citizenship in the First World War1. (11th April 2014) - Reilly, Kimberley A.
<x content-type="archive" xml:space="preserve">Abstract</x> This essay examines the influence of the social purity movement on the U.S. government's campaign to protect servicemen from the temptations of drink and illicit sex during World War I. This influence had been forged in the context of U.S. imperialism in the two decades prior to American entry into the war, as purity reformers linked the sexual morality and temperance of soldiers serving in occupied territories overseas to racial purity and national character at home. War Department policymakers who were allied with the purity movement likewise understood male moral restraint and sexual self-control to underpin democratic self-governance. This linkage between civic virtue and moral virtue was especially problematic at the outset of the war, as many native-born Americans (progressive policymakers included) questioned whether all members of the ethnically and racially diverse nation had the capacity for self-government. The goals of social purity and wartime policymakers were thus aligned as the War Department launched its crusade against liquor and sexual vice within the military. Government officials required moral sobriety of servicemen in order to remake the body politic. But even as they demanded virtuous conduct from the man in uniform, they simultaneously infantilized the "soldier lad" in their effort to safeguard him.